RETRACTED: The influence of socio-ecological and economic factors on sustainable development in the context of the economy of intelligence - Idigova Lalita; Zakhokhova Madina; Galinskaya Natalya; Chaplaev Khusein; Akoeva Raisa (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001